Success in Online Courses: Instructors’ Perception of Caring Practices for Adult Students - Damiao Zoe Xu; Robin Grenier PhD (Adult Education Research Conference, 2025)
This session presents a pilot study that explores instructors’ perceptions of care for adult students in online courses, and relationship between their perceptions and experience as an adult student.
Keywords: instructor; adult student; online; support